Laboratory Evaluation of Insecticides as Contact Sprays against forest Pests. II-ailanthus webworm: Atteva fabriciella Swed. (Lepidoptera: Yponomeutidae - Singh, Pratap; Gupta, B. K. (Indian Forester, 1978)
Twenty insectides were tested as contact poisons againat the 3rd instar larvae of Atteva Jabriciella the Ailanthus webworm. Out of this two insecticides viz., Anthio and Chlordimeform proved most effective in comparision to D.D.T, while Quinalphos and Monocrotophos also proved 36.0974 and 22.9218 times more effective than D.D.T., Pyrethurum, Carbaryl and Fenitrothion also proved 13.7231, 13.2100, 10.0963 times more effective when compared with D.D.T. Rest of the Insecticides can be put according to their effectiveness in descending order as Leptophos, Dichlorvos, Cythion, Ambithion, Endosulfan, Endrin, Gama B.H.C., D.D.V.P., dimethoate, Malathion, Aldrin, Dieldrin & D.D.T.